Quantification of pulmonary/systemic shunt ratio by single‐acquisition phase‐contrast cardiovascular magnetic resonance. Issue 6 (13th May 2019) - Dunn, Terence Sean; Patel, Pratik; Abazid, Bassem; Nagaraj, Hosakote M.; Desai, Ravi V.; Gupta, Himanshu; Lloyd, Steven G.
Abstract: Purpose: Phase‐contrast cardiovascular magnetic resonance (PC‐CMR) quantification of intracardiac shunt (measuring the pulmonary to systemic flow ratio, Qp/Qs) is typically determined by measuring flow through planes perpendicular the pulmonary trunk (PA) and ascending aorta (Ao). This method is subject to error from presence of background velocity offsets and requires two scan acquisitions. We evaluated an alternate PC‐CMR technique for quantifying Qp/Qs using a single modified plane that encompasses both the PA and Ao. Material and Methods: In 53 patients evaluated for intracardiac shunting, PC‐CMR measurement in the individual Ao and PA planes and also in a single‐acquisition plane was obtained and Qp/Qs calculated by each method. Bland–Altman analysis was performed to evaluate the agreement between the two methods. Results: The 95% confidence limits of agreement ranged from −0.52 to +0.34 indicating good agreement between the two methods. There was excellent agreement on the clinically relevant threshold value of Qp/Qs ratio of 1.5 (representing criteria for surgical correction of shunt). Conclusions: Qp/Qs determined from the single‐acquisition approach agrees well with that of the individual PA and Ao method and offers potential improved accuracy (due to background velocity offset).